Inconsistency in Recognition and Enforcement of Foreign Arbitral Awards: Non-Compliance or Normative Factors? - Taqwa, Muhamad Dzadit; Laksmi Prabhaswari, Amaraduhita; Putri Subiyanto, Maria Jasmine (Faculty of Law Universitas Padjadjaran, 2024)
Recognizing and enforcing a foreign arbitral award has been becoming a global issue. To solve such an issue, the New York Convention 1958 turns out to be an important international legal product regarding the recognition and enforcement of foreign arbitral awards worldwide. States ratifying the convention are internationally bound to respect and assist in the execution of a foreign arbitration award in their respective countries; Indonesia is one of them. It ratified the convention by Presidential Decree Number 34 of 1981. Nonetheless, there is an impression that Indonesia has not implemented the convention consistently, compared to countries that are, considered, friendly to foreign arbitration awards due to the facts that there are several foreign arbitral awards that have been rejected by the District Court. This impression, however, needs to be re-examined by understanding textually the norm formula in the 1958 New York Convention and comparing its implementation among Indonesia and several countries that are considered friendly to foreign arbitration awards. This paper finds that there is a norm formula in the 1958 New York Convention that opens space for ratification countries not to always recognize and enforce foreign arbitral awards in the executing country of the award.